Gastropod Pests on Gracilaria Cylindrica and Gracilaria Verrucosa - Eddy Soekendarsi (Masyarakat Moluska Indonesia, 2019)
Using traditional methods, Gracilaria cylindrica and Gracilaria verrucosa are commonly cultivated in ponds located in the south eastern parts of South Sulawesi. G. cylindrica has thick, cylindrical branches. G. verrucosa has slender broad-based branches. An illustrated taxonomic account is presented. Three species of herbivore gastropods, Clithon sp., Neritodryas sp., and Clypeomorus sp., occur naturally in the pond areas. The snails easily develop into pests. To reduce the problem, farmers must daily clean cultured Gracilaria by hand. Polyculture of Gracilaria and milk fish reduce problems with fouling epiphytes.